2010
DOI: 10.1038/mp.2010.120
|View full text |Cite
|
Sign up to set email alerts
|

The GABAergic deficit hypothesis of major depressive disorder

Abstract: Increasing evidence points to an association between major depressive disorders (MDDs) and diverse types of GABAergic deficits. Here we summarize clinical and preclinical evidence supporting a central and causal role of GABAergic deficits in the etiology of depressive disorders. Studies of depressed patients indicate that MDDs are accompanied by reduced brain concentration of the inhibitory neurotransmitter γ-aminobutyric acid (GABA) as well as alterations in the subunit composition of the principal receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
557
3
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 765 publications
(636 citation statements)
references
References 376 publications
34
557
3
9
Order By: Relevance
“…These findings suggest that antidepressant treatment can normalize the dysfunction of the GABAergic system (Luscher et al, 2011), which may lead to the increase in GABA release observed in patients (Carter and McCormack, 2009;Sanacora et al, 2002). Collectively, animal and clinical studies indicate that a deficit for GABAergic activity may be crucial in the pathophysiology of mood disorders, and that effective modulation of GABAergic transmission may represent another important mechanism through which antidepressant drugs exert their therapeutic activity (Luscher et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings suggest that antidepressant treatment can normalize the dysfunction of the GABAergic system (Luscher et al, 2011), which may lead to the increase in GABA release observed in patients (Carter and McCormack, 2009;Sanacora et al, 2002). Collectively, animal and clinical studies indicate that a deficit for GABAergic activity may be crucial in the pathophysiology of mood disorders, and that effective modulation of GABAergic transmission may represent another important mechanism through which antidepressant drugs exert their therapeutic activity (Luscher et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Parvalbumin alteration in hippocampal interneurons may lead to a loss of perisomatic inhibition of pyramidal neurons, which in turn affects network synchronization and memory formation (Bartos et al, 2007;Lewis et al, 2005). Disturbances in the anatomy and function of the GABAergic system have been postulated in animal models of depression and in different stress-related psychiatric disorders (Benes and Berretta, 2001;Brambilla et al, 2003;Krystal et al, 2002;Luscher et al, 2011;Sanacora et al, 1999). In fact, GABA A receptors can be downregulated in different brain regions of rats exposed to the learned helplessness paradigm (Drugan et al, 1992), whereas lower CSF and plasma GABA levels have been found in depressed patients, as compared with control subjects (Gerner et al, 1984;Gerner and Hare, 1981;Kasa et al, 1982;Petty et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ther. 2007 or recent papers [3][4][5][6] ). Unlike the family of other steroid hormones, neurosteroids do not bind to nuclear but to membrane receptors for neurotransmitters.…”
Section: Introductionmentioning
confidence: 99%